Prevalence of Psychiatric Disorders among Children and Adolescents: A Study from Khuzestan - Riahi, Frough; Mohammadi, Mohammad Reza; Izadi, Maryam; Khaleghi, Ali; Hooshyari, Zahra (Iranian Journal of Child Neurology, 2022)
Objective This cross-sectional study aimed to study the prevalence rate of psychiatric disorders in children and adolescents in Khuzestan province. Materials & Methods A community sample consisting of 1028 (51.6% female) children and adolescents aged 6-18 years was selected using a multistage cluster sampling method. Data were gathered using the Kiddie-SADSPresent and Lifetime Version (K-SADS-PL) and a demographic questionnaire (i.e., gender, age, level of education, place of residence, parent’s education, and parent’s Job) Results Nearly 22.6% (22.3% of boys and 23% of girls) of all participants suffered from at least one psychiatric disorder. There was no significant difference in the prevalence of psychiatric disorders based on gender, age, father’s education, mother’s education, mother’s job, and father’s job (all p>0.05). Psychiatric disorders were significantly more prevalent among children and adolescents in urban areas compared to rural places (2.9% vs. 8.1; p<0.001). The most prevalent category was anxiety disorders (15%). Also, the most common disorders were specific phobia (7%), separation anxiety disorder (6.3%), and enuresis (5.2%). The most common comorbid disorders were mood disorders and anxiety disorders (56.3%), followed by anxiety disorders and elimination disorders (32.1%). Conclusion Psychiatric conditions are prevalent in children and adolescents living in Khuzestanian. The study’s findings have important implications for providing effective psychiatric services.